2019
DOI: 10.1080/10942912.2019.1666871
|View full text |Cite
|
Sign up to set email alerts
|

Organic magnesium salts fortification in fermented goat’s milk

Abstract: The aim of this study was the production of a functional goat's milk product fortified with organic magnesium salts and fermented by Bifidobacterium Bb-12. The best stimulator of probiotic bacteria growth was magnesium citrate. Fermented milk with citrate addition had a similar L*a*b* color parameters in comparison to the control milk sample. The addition of magnesium pidolate significantly favorably increased the hardness of the fermented milk; however, the fortification with magnesium lactate and citrate dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 39 publications
1
19
1
9
Order By: Relevance
“…The composition and physicochemical characteristic of raw goat’s milk is presented in Table 1 . The protein, fat and total solids values were higher than those reported by Barłowska et al [ 5 ], Wolanciuk et al [ 41 ] and Znamirowska et al [ 40 ] for White improved goat breed milk and milk from unidentified goats. The gross chemical composition was, however, in accordance with that reported by Guo et al [ 42 ] for commingled goat milk.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…The composition and physicochemical characteristic of raw goat’s milk is presented in Table 1 . The protein, fat and total solids values were higher than those reported by Barłowska et al [ 5 ], Wolanciuk et al [ 41 ] and Znamirowska et al [ 40 ] for White improved goat breed milk and milk from unidentified goats. The gross chemical composition was, however, in accordance with that reported by Guo et al [ 42 ] for commingled goat milk.…”
Section: Resultscontrasting
confidence: 62%
“…The concentration of macro-and microelements (Ca, K, Mg, P, Mn, Se, Cd and Pb) in milk, cheese and whey was determined by ICP-OES (inductively coupled plasma-optical emission spectrometry) method with a spectrophotometer Thermo iCAP Dual 6500 (Thermo Fisher Scientific Inc., USA) according to Znamirowska et al [40] with modifications (2.50 g of milk, 1.00 g of whey and 0.50 g of cheese were weighed). The ICP-OES instrument was calibrated with standards (Merck, Darmstadt, Germany) including concentrations of 10,000 ppm for macroelements and 1000 ppm for microelements.…”
Section: Mineral Composition Of Milk Cheese and Wheymentioning
confidence: 99%
“…Texture profile analysis (TPA) was performed according to the method of Znamirowska et al [19]. Parameters of the texture were determined using the Brookfield CT3 Texture Analyzer.…”
Section: Instrumental Texturementioning
confidence: 99%
“…The TBC (total bacterial count) showed in Table 1 is much lower, which indicates that the evaluated milk meets the criteria of Regulation 1662/2006 [ 36 ]. Znamirowska et al [ 37 ] determined a lower bacterial cell count (120,500 CFU mL −1 ) in goat milk. Another study reported TBC in goat milk of 359,000 CFU mL −1 [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The specific properties of goat milk form the different texture and rheological properties of fermented milk compared to fermented cow milk [ 54 , 55 , 56 ]. According to Znamirowska et al [ 37 ], some mineral compounds added to milk before pasteurization can improve the textural properties of milk acid gels.…”
Section: Resultsmentioning
confidence: 99%